Analisis Faktor-Faktor Yang Mempengaruhi Intensi Berwirausaha Mahasiswa Akuntansi Universitas Sarjanawiyata Tamansiswa Yogyakarta - Adia Adi Prabowo (Forum Dosen Indonesia, 2021)
The purpose of this study was to examine the influence of personal attitudes, subjective norms, behavior, behavior, and the environment on the interest in entrepreneurship. This type of research is descriptive quantitative while the sampling in this study using purposive sampling of 232 students. The data analysis method was carried out using PLS-SEM analysis, testing PLS-SEM analysis through two stages, namely the measurement model (Outer Model) and the structural model (Inner Model). The results of this study indicate that: personal attitudes, behavioral control and entrepreneurial skills have a positive influence on interest in entrepreneurship. Meanwhile, university environment variables and norms do not have a positive influence on entrepreneurial interest.